A Contrastive Analysis Study Between English and Batak Toba in Request Sentence - Ezra Octania Sianipar; Herman Herman; Ridwin Purba (Edu-Ling: Journal of English Education and Linguistics, 2022)
This study examines the English and Toba Batak language request sentence. The imperative phrase of both languages from its form, purpose, and category in a sentence was studied in this analysis. The research used descriptive approach and contrastive analysis in terms of methods, the entire data were gathered by observing and interviewing the native speakers of Toba Batak dialects who still speak in their everyday communication. In the analysis, the authors outlined and compared the differences and similarities in request sentences. The result that we saw from the position of the subject In Toba Bataknese, the position of subject was flexible, they could change without changing the meaning. While in English the position of subject was stable. In the request sentence, Batak Toba is less harsh and Batak people rarely use the word please, and usually the intonation seems strong and there is emphasis, while the request sentence is more likely to be smooth and polite, and the intonation is smoother.